USP39 promotes non-homologous end-joining repair by poly(ADP-ribose)-induced liquid demixing. Issue 19 (6th October 2021) - Kim, Jae Jin; Lee, Seo Yun; Hwang, Yiseul; Kim, Soyeon; Chung, Jee Min; Park, Sangwook; Yoon, Junghyun; Yun, Hansol; Ji, Jae-Hoon; Chae, Sunyoung; Cho, Hyeseong; Kim, Chan Gil; et al.
Abstract: Mutual crosstalk among poly(ADP-ribose) (PAR), activated PAR polymerase 1 (PARP1) metabolites, and DNA repair machinery has emerged as a key regulatory mechanism of the DNA damage response (DDR). However, there is no conclusive evidence of how PAR precisely controls DDR. Herein, six deubiquitinating enzymes (DUBs) associated with PAR-coupled DDR were identified, and the role of USP39, an inactive DUB involved in spliceosome assembly, was characterized. USP39 rapidly localizes to DNA lesions in a PAR-dependent manner, where it regulates non-homologous end-joining (NHEJ) via a tripartite RG motif located in the N-terminus comprising 46 amino acids (N46). Furthermore, USP39 acts as a molecular trigger for liquid demixing in a PAR-coupled N46-dependent manner, thereby directly interacting with the XRCC4/LIG4 complex during NHEJ. In parallel, the USP39-associated spliceosome complex controls homologous recombination repair in a PAR-independent manner. These findings provide mechanistic insights into how PAR chains precisely control DNA repair processes in the DDR.